Local Formation of InAs Nanocrystals in Si by Masked Ion Implantation and Flash Lamp Annealing. Issue 12 (13th October 2017) - Rebohle, Lars; Wutzler, René; Prucnal, Slawomir; Hübner, René; Georgiev, Yordan M.; Erbe, Artur; Böttger, Roman; Glaser, Markus; Lugstein, Alois; Helm, Manfred; Skorupa, Wolfgang
Abstract : The integration of high‐mobility III–V compound semiconductors emerges as a promising route for Si device technologies to overcome the limits of further down‐scaling. In this work, we investigate the possibilities to form InAs nanocrystals in a thin Si layer at laterally defined positions with the help of masked ion beam implantation and flash lamp annealing. In detail, a cladding layer was deposited on a silicon‐on‐insulator (SOI) wafer and patterned by electron beam lithography in order to serve as an implantation mask. The wafer was subsequently implanted with As and In, followed by flash lamp annealing leading to the formation of InAs nanoparticles in the implanted areas. The structures were investigated by Raman spectroscopy, scanning, and transmission electron microscopy as well as energy‐dispersive X‐ray spectroscopy. Depending on the size of the implantation window, several, one or no nanoparticle is formed. Finally, the perspectives for using this technique for the local modification of Si nanowires are discussed. Abstract : InAs nanocrystals are formed in a thin Si device layer at laterally defined positions by electron beam lithography, masked ion beam implantation and flash lamp annealing. Depending on the size of the implantation window, several, one or no nanoparticle is formed. Finally, the pro and cons of this technique for the local modification of Si nanowires are discussed.